БОШЛАНҒИЧ СИНФ ЎҚИТУВЧИСИНИНГ АХБОРОТ КОММУНИКАТИВ КОМПЕТЕНТЛИГИНИ РИВОЖЛАНИШ КОМПОНЕНТЛАР («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article describes the components of the development of information and communication competence of a primary school teacher and their indicators.
Keywords: Competent, expert, informational, communicative, motivational, research, activity, operational, cognitive, control, corrective, reflective, predictive.